STUDY OF PHYSICAL ENVIRONMENT BASED ON LAND SYSTEM MAP OF KABUPATEN BANDUNG - Mukhtar, Mutia Kamalia; Nurwadjedi, Nurwadjedi (UI Scholars Hub, 2019)
The environmental damage in Kabupaten Bandung is critical. To solve the environmental problems, the integrated spatial data of the physical environment is required. Land system data as the integrated spatial data which describes the characteristics of land are useful for the analysis and evaluation of the environmental conditions. The objective of the study is to describe the characteristics of the physical environment of Kabupaten Bandung based on the land system map for the input of decision-making in achieving sustainable development. The study used the spatial analysis and descriptive analytical method. The land system data was obtained from the Badan Informasi Geospaasial (BIG). The results show that the landforms in Kabupaten Bandung are dominated by volcanic and fluvial landforms. The volcanic landforms has morphology dominated by mountainous areas with the slope steepness more than 45% and the soil types of andosols. The land capability of these mountainous areas belongs to grade 7 (for conservation areas). The fluvial landforms are lacustrine plains, which are prone to flood due to inundation. From this study, it is concluded that the land utilization in Kabupaten Bandung, particularly in mountainous areas, is not in accordance with the land carrying capacity. To achieve the sustainable development, the land utilization should consider the regulation of spatial planning, by which the lands with slope steepness more than 40% are categorized as protected areas.